1988
DOI: 10.1007/bf00582380
|View full text |Cite
|
Sign up to set email alerts
|

Gamma glutamyltransferase contribution to renal ammoniagenesis in vivo

Abstract: The role of gamma-glutamyltransferase (gamma-GT) in renal ammoniagenesis and glutamine utilization was evaluated in the intact functioning rat kidney. Total NH4+ released, as the sum of renal venous and urinary NH4+, was measured under conditions of chronic metabolic acidosis and paraminohippurate infusion. Ammonia derived from extracellular gamma-GT hydrolysis of glutamine was differentiated from that produced by intracellular phosphate dependent glutaminase (PDG) by employing acivicin, a gamma-GT inhibitor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…Rats were killed by an overdose ofthe anesthetic. The resulting arterial para-aminohippuric acid concentrations (< 70 MM) are not likely to influence renal ammoniagenesis ( 15). Also, our urine data in control rats are comparable to studies in which no para-aminohippuric acid was used ( 15,16), providing evidence for the reliability of this urine sampling method.…”
Section: Methodssupporting
confidence: 74%
“…Rats were killed by an overdose ofthe anesthetic. The resulting arterial para-aminohippuric acid concentrations (< 70 MM) are not likely to influence renal ammoniagenesis ( 15). Also, our urine data in control rats are comparable to studies in which no para-aminohippuric acid was used ( 15,16), providing evidence for the reliability of this urine sampling method.…”
Section: Methodssupporting
confidence: 74%
“…The results of these studies revealed, however, no sub stantial role of y-GT in total renal ammonia genesis under control and acidotic conditions [3,[23][24][25][26], which is in agreement with the rates of utilization of glutamine by y-GT, and is in good accord with our findings on LLC-PK, epithelia ( fig. 2.…”
Section: Discussionsupporting
confidence: 82%
“…This particular role of the hydrolytic activ ity of y-GT in the extracellular splitting of glu tamine and luminal ammoniagenesis, respec tively, has been studied recently in detail in vivo [23][24][25][26] and in vitro [34,35]. The results of these studies revealed, however, no sub stantial role of y-GT in total renal ammonia genesis under control and acidotic conditions [3,[23][24][25][26], which is in agreement with the rates of utilization of glutamine by y-GT, and is in good accord with our findings on LLC-PK, epithelia ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Welbourne" investigated the enhanced renal ammoniagenesis in a study of chronic acidosis in rats. Increased urinary ammonia excretion was observed at elevated arterial ammonia levels.…”
Section: Lungmentioning
confidence: 99%